THE INFLUENCED OF BRAND EQUITY AND CUSTOMER SATISFACTION OF CUSTOMER LOYALTY TO IMPROVING IN HOSPITAL MARTHA FRISKA - Chairiza, Annisa (Universitas Harapan Medan, 2025)
This research was conducted at the hospital Martha Friska engaged in health services for the community. With competition getting tougher in the field hospital, the hospital management was required to give the best to meet the needs of consumers. To that end, the hospital management Martha Friska seeks to preserve and maintain the brand equity that has been well established in the community and provide satisfaction as expected consumers so that consumers remain loyal in the use of health services from hospitals Martha Friska. The purpose of this study to examine and analyze the effect of brand equity and customer satisfaction partially and simultaneously to increase consumer loyalty Martha Friska Hospital Medan. This type of research was associative. The research sample using a random sample with a sample size of 100 respondents. Sources of data research using primary data with data collection using surveys. Data were analyzed using multiple linear regression. Based on the research results show that partial and simultaneous brand equity and customer satisfaction positively and significantly to the improvement of customer loyalty in the hospital Martha Friska. In correlation determination shows that the brand equity and customer satisfaction has a very strong influence on the increase of consumer loyalty Martha Friska field hospital that was equal to 71.4%.